Experimental Study on Minimum Quantity Lubrication in End Milling of AA6061-T6 Using Tialn Coated Carbide Tools - Najiha, M. S.; M. M., Rahman (Universiti Malaysia Pahang, 2015)
This paper presents an experimental investigation on the effects of output parameters during machining of aluminum alloy 6061-T6 using the minimum quantity lubrication (MQL) technique through end milling processes. In this study cutting speed, depth of cut, feed rate and MQL flow rate are selected as input parameters. Experiments are conducted using the central composite design method. Statistical models for process optimization are obtained using the response surface method. The objective of the study is to investigate and optimize the process parameters employing coated carbide cutting tools; coatings used are TiAlN. For the purpose of the study, surface roughness and material removal rate are selected as response variables. The results of the study show that the inserts coated with TiAlN perform very well, showing good machinability. According to the results of the study, MQL can easily be a suitable eco-friendly alternative to conventional flood cooling conditions. MQL proves to be more beneficial with the application of coated tools in end milling of aluminum alloys.